Pelatihan Pembuatan Bahan Ajar Interaktif VBA Untuk Kompetensi Guru Sebagai Rekonsiliasi Edukatif Dan Mathematical Entrepreneurship - Linda, Linda (ABJIS: Al-Bahjah Journal of Islamic Community Service, 2025)
The implementation of education in Indonesia has entered the digital era (digital society), especially online learning is carried out with the help of technology through various Android applications, computers/laptops so mastery of the use of technology is really needed for teachers. However, one of the problems in learning is the teacher's skills in mastering and using digital for learning activities, creating interactive teaching materials as a reconciliation of education and entrepreneurship. The aim of this service is to provide training in making VBA-based interactive teaching materials for teachers at SMP Negeri 32 Bandung, with a total of 10 teachers. The method used is classical by providing theoretical and practical material regarding the creation of interactive teaching materials with steps to identify problems, solve problems (preparation stages, implementation stages and evaluation). In the final stage, it continues with the individual method of providing individual direction to the teacher so that they can develop the work of the teaching materials to be used as a target for entrepreneurship to produce a profit. As a result of this service activity, a high positive and enthusiastic response was obtained from teachers so that it is hoped that school agencies or educational institutions will have the assets to continue to develop teachers' potential in mastering digital so that it can be applied in learning and entrepreneurship activities.